Phylogeography of North American herbaceous Smilax (Smilacaceae): Combined AFLP and cpDNA data support a northern refugium in the Driftless Area1. Issue 4 (1st April 2013) - Li, Pan; Li, Mimi; Shi, Yin; Zhao, Yunpeng; Wan, Ying; Fu, Chengxin; Cameron, Kenneth M.
Abstract : Premise of the study: The genetic structure of North American herbaceous Smilax, a clade of closely related understory herbs that has a wide and disjunct distribution, was investigated to test the hypothesis of whether a northern refugium in the upper Midwest may have existed for these plants during the last glaciation. Methods: We analyzed 33 populations sampled from California and throughout the eastern United States using AFLP and chloroplast DNA sequence data. Key results: Individuals of S. jamesii from northern California formed a clade sister to the eastern North American species, and they likely diverged from each other during the Pleistocene. Among the eastern species, two lineages were found on opposite sides of the Appalachian Mountains. The populations near the "Driftless Area" contained most of the chlorotypes found in the Midwest, including a unique one endemic to this area, and the AFLP data indicated that one population from this area has the highest frequency‐down‐weighted‐marker value. Conclusions: This study, and others that have focused on mammals, amphibians, and woody plants, provides further evidence for the debate over whether the upper Midwest's "Driftless Area" may have hosted a biologically diverse northern glacial refugium. Herbaceous species of Smilax from eastern North American exhibit an Appalachian discontinuity. They appear to have persisted in multiple refugia both east and west of the Appalachians, with several populations persisting in situ through the Last Glacial Maximum (LGM). We suggest that they experienced localized expansion after the LGM, possibly followed by subsequent contact between the Midwest and the East Coastal lineages.